SWOT Strategy for Increasing Sales at "Bakso Bangkit Jember" - Haryono, Rudi; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Micro Business is one of the biggest driving sectors in Jember Regency. The authority of the Jember Regency government is only in the micro business sector. Currently, the Jember Regency government is more focused on growing new entrepreneurs and developing businesses with various kinds of training, technical guidance and product diversification in order to improve the economy of the Jember community. The aim of this research is to find out how the marketing strategy of Bakso Bangkit Jember business actors increases their turnover. The type of research is qualitative with data collection methods namely interviews, documentation and observation as well as SWOT analysis. The results of this research show that the strategic analysis carried out was very effective and the SWOT analysis was applied to increase turnover in the "Bakso Bangkit Jember" business, namely by innovating and modifying ingredients, maintaining or improving product quality and promoting products both offline and online.